COMPARATIVE ANALYSIS OF CASE-TOOLS FOR LABORATORY INFORMATION SYSTEMS IN THE MINING INDUSTRY - Nosirovich, Rozikulov Aziz; Drebenstedt, Carsten; Nosirovich, Rozikulov Abrorkhon; Burievich, Toshov Javokhir; Stepanek, Rodica Cujba (FUDMA Journal of Sciences, 2026)
LIMS (Laboratory Information Management System) in the mining industry must support the entire cycle of laboratory processes, from sample collection, registration and tracking to analytical testing, calculation of ore quality indicators and generation of regulated reports. The system must ensure integration with the enterprise's corporate information circuits (ERP, MES, SCADA), support the requirements of ISO 9001 and ISO/IEC 17025 standards, and guarantee the reliability, integrity and traceability of data. In these conditions, the use of CASE tools becomes particularly important, as they enable initial process modelling, formalisation of laboratory business processes, documentation of system architecture, requirements and change management, and automatic generation of project documentation. CASE tools should provide visual process description (BPMN/UML/IDEF), bottleneck analysis, simulation modelling of laboratory workload, performance evaluation, as well as support for versioning and change control.This study aims to provide a comparative analysis of modern CASE tools in terms of their applicability for the design and implementation of LIMS in the mining industry. The functional capabilities, ease of modelling, integration mechanisms, support for standards, scalability, and cost-effectiveness of the solutions are evaluated. The results of the analysis allow us to justify the choice of the optimal tool for developing a reliable, manageable laboratory information system that meets industry requirements.
Keywords: LIMS; CASE tools; process modelling; Laboratory business processes; mining industry